2013
DOI: 10.2215/cjn.08780812
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Male Dialysis Patients for Fabry Disease by Plasma Globotriaosylsphingosine

Abstract: Summary Background and objectives Previous reports of Fabry disease screening in dialysis patients indicate that α-galactosidase A activity alone cannot specifically and reliably identify appropriate candidates for genetic testing; a marker for secondary screening is required. Elevated plasma globotriaosylsphingosine is reported to be a hallmark of classic Fabry disease. The purpose of this study was to examine the usefulness of globotriaosylsphingosine as a secondary screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…A couple of studies investigated the frequency of FD in dialysis [12][13][14][22][23][24][25] and the results showed that the average prevalence rate of FD in dialysis was about 0.37% [26]. It was too late to diagnose new FD patients until they were on HD.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies investigated the frequency of FD in dialysis [12][13][14][22][23][24][25] and the results showed that the average prevalence rate of FD in dialysis was about 0.37% [26]. It was too late to diagnose new FD patients until they were on HD.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports on the frequency of Fabry diseaseinduced dialysis patients, but these were not necessarily examined using a sufficient number of dialysis patients [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. With respect to the clinical diagnosis of ESKD in dialysis patients, the frequency of diabetic nephropathy, chronic glomerulonephritis, nephrosclerosis, etc., is high; however, cases in which the clinical diagnosis of ESKD is unknown are also frequent at about 7.8 % in Japan [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the plasma lyso-Gb3 screen identified FD with high sensitivity (100%) and specificity (94.3%), with a prevalence of FD in male dialysis patients of 0.07% [37].…”
Section: Screening and Prevalence Of Fabry Nephropathymentioning
confidence: 73%
“…With a different approach, Maruyama et al [37] performed the first screening of dialysis patients for FD by measuring plasma Gb3 (lyso-Gb3), which has been shown to be clearly increased in the plasma of patients with symptomatic FD [38]. In this study, the plasma lyso-Gb3 screen identified FD with high sensitivity (100%) and specificity (94.3%), with a prevalence of FD in male dialysis patients of 0.07% [37].…”
Section: Screening and Prevalence Of Fabry Nephropathymentioning
confidence: 80%